﻿Le philosophe chez Vélasquez : l’intrusion de Michel Foucault dans la fortune critique des Ménines - Dubreuil-Blondin, Nicole (RACAR : Revue d'art canadienne / Canadian Art Review, 1993)
This article compares Michel Foucault's analysis of Velazquez' Las Meninas and the critical production inspired by the approach of the philosopher with the more conventional interpretation of the work by specialists of Spanish painting. Examining in detail the diverging strategies of the “theoreticians” and the “scholars,” it attempts to map out the conceptual horizon as well as the methodological procedures of both camps.One important point of divergence between the two groups is the result of Foucault's interest in the “apparatus” of the painting, as opposed to a concern for its narrative and symbolic content. This implies a passage from the “what” to the “how” of representation, from reference to self-reference and a privileging of structural functions over or before considerations of social status.The study also considers some repressed elements in the Foucauldian approach, from gender relations to the pictorial treatment of the work.